Physiological and morpho-anatomical analyses of hyperhydric Arabidopsis thaliana influenced by media components - Kemat, Nurashikin; Visser, Richard G. F.; Krens, Frans A. (Korean Society for Plant Biotechnology, 2023)
Hyperhydricity is a physiological anomaly that significantly affects the growth and proliferation rate of crops cultivated by tissue culture techniques. To better understand the mechanisms that govern hyperhydricity incidence, we examined the effects of several media components, particularly cytokinin and gelling agents. These elements were found to be influential in both in vitro propagation and the development of hyperhydricity. Our study revealed that Arabidopsis thaliana seedlings had a greater manifestation of hyperhydricity symptoms when exposed to high cytokinin concentrations compared with the control. The presence of gelrite led to the manifestation of hyperhydric symptoms by elevated water build-up in the apoplast. The phenomenon of stomata closure was observed in the hyperhydric leaves, resulting in an increased ability to retain water and a decrease in the transpiration rates when compared to their respective control leaves. Additionally, histological examinations of the cross sections of hyperhydric leaves revealed an irregular cellular arrangement and large intercellular spaces. Furthermore, hyperhydric seedlings displayed impaired cuticular development in comparison to their normal seedlings.